Molecular Investigation of an Ontario Mumps Outbreak using Whole Genome Sequencing. (4th October 2017) - Stapleton, Patrick; Eshaghi, Alireza; Chong-King, Eddie; Cardona, Mark; Masney, Steve; Li, Aimin; Gubbay, Jonathan; Patel, Samir
Abstract: Background: In early 2017 an outbreak of Mumps virus affected over 100 individuals in the province of Ontario, concurrent with multiple mumps virus outbreaks across North America. Traditional genotyping of mumps outbreaks relies on sequencing a portion of the small hydrophobic (SH) gene, but has limited capability to distinguish between strains of the same genotype. Most mumps cases in Ontario in recent years are of genotype G. We used a novel whole genome sequencing (WGS) protocol to perform a molecular epidemiological investigation of the outbreak. Methods: Throat ( n = 5) and buccal ( n = 15) swabs positive by RT-PCR for SH or Fusion (F) gene targets were cultured in primary Rhesus monkey kidney cells. Cell free viral extract underwent RT-PCR and subsequent PCR amplification using overlapping primer pairs to cover the entire 15 kilobase (kb) genome. The first 8 samples were amplified with 18 pairs of overlapping primers, which was reduced to 9 sets (average fragment size 1.9 kb, range 1.6–2.8 kb) for the final 12 samples. Mumps cDNA libraries were prepared with Nextera XT kit and WGS of the indexed fragments was performed with V2 reagent kits on the Illumina MiSeq instrument. Reference based genome assembly was performed using samtools version 1.4. Phylogenetic analysis was performed by maximum likelihood method in MEGA7. Results: We identified two distinct genotype G lineages comprised of 9 patients each and closely related to a 2009–2010 outbreak in Ontario and New York (Figure 1). Inter-lineage single nucleotide polymorphism (SNP) differences ranged from 25 to 31, whereas intra-lineage SNPs ranged from 0 to 8 SNPs. Two outlying sequences, of genotype C and G respectively, may represent sporadic introduction of virus from other areas. Time from virus isolation to SNP based analysis was approximately 4 days. Conclusion: WGS of Mumps virus culture isolates using the PCR fragment method identified two distinct genotype G lineages in a large provincial outbreak. This method may aid public health authorities identify separate transmission chains in the case of large outbreaks. Disclosures: All authors: No reported disclosures.